Making sustainable finance sustainable - Peterson K. Ozili (Financial Internet Quarterly, 2021)
The purpose of this paper is to highlight some issues and proffer solutions that can make sustainable finance become sustainable. One, there should be greater focus on how some aspects of finance can contribute to sustainability. Two, light-touch regulation may be needed to grow the relatively small sustainable finance sector. Three, there is a need to adopt a bottom-up approach to grow the sustainable finance sector. Four, voluntary ESG disclosures and related sustainability reporting should be encouraged. Five, short-term financial instruments can complement long term instruments in sustainable financing.
Keywords: Q01; G21; G28; 330; finance; sustainability; financial institutions; financial instruments; green finance; green bonds; light-touch regulation; bottom-up approach; sustainability reporting; sustainable development